Japan : Selected Issues. (IMF Staff Country Reports; Country Report, 2016)
This Selected Issues paper discusses the findings of the IMF staff research focusing on labor market dynamics, economic growth, the financial sector, private investment, and monetary policy in Japan. Japan's labor market has fared relatively well considering the occasional substantial output losses, with unemployment remaining low. Although Japan's employment responsiveness to the cyclical position has been relatively low, it has been rising over time reflecting the higher share of the nonregular workforce. The lower employment response to output compared with other countries during the Great Recession reflects the quick implementation of an employment subsidy program, a more flexible wage system, and strong employment protection.